2018
DOI: 10.3390/app8071050
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization Dynamics of Slow Highly Charged Ions in 2D Materials

Abstract: We review experimental and theoretical work on the interaction of slow highly charged ions with two-dimensional materials. Earlier work in the field is summarized and more recent studies on 1 nm thick amorphous carbon nanomembranes and freestanding single layer graphene by the authors are reviewed. To explain the findings, models for energy loss determination as well as qualitative model descriptions for the observed ultrafast neutralization dynamics are discussed. The results shown in this paper will be put i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 70 publications
(107 reference statements)
0
10
0
Order By: Relevance
“…Many studies have demonstrated the ability of first-principles calculations to predict accurate energy deposition rates for ions traversing bulk materials [23][24][25][26][27][28][29]. However, projec-tile charge may not fully equilibrate within a thin target [30][31][32], fundamentally altering the response of these materials to ion irradiation. More recently, several studies considered ion-irradiated surfaces and 2D materials [33][34][35][36][37][38], in some cases predicting enhanced energy deposition compared to bulk caused by surface plasmon excitations [33] or mediated by projectile charge capture processes [37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have demonstrated the ability of first-principles calculations to predict accurate energy deposition rates for ions traversing bulk materials [23][24][25][26][27][28][29]. However, projec-tile charge may not fully equilibrate within a thin target [30][31][32], fundamentally altering the response of these materials to ion irradiation. More recently, several studies considered ion-irradiated surfaces and 2D materials [33][34][35][36][37][38], in some cases predicting enhanced energy deposition compared to bulk caused by surface plasmon excitations [33] or mediated by projectile charge capture processes [37].…”
Section: Introductionmentioning
confidence: 99%
“…Graphene in particular has high carrier mobilities and weak electron-phonon coupling, suggesting that electronic excitations would delocalize too quickly to damage the atomic structure. Accordingly, simulations of highly charged ions impacting a graphene layer represented as jellium [32,39] predicted very large cur-rent densities which quickly spread electronic excitations throughout the material, preventing damage. Nonetheless, experiments find large, nanoscale defects in few-layer carbon materials after irradiation by highly charged ions [40][41][42], where localized electronic excitations are postulated to cause strong Coulombic repulsion of unscreened nuclei or weaken atomic bonds which then interact with the ambient environment.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Such studies inferred projectile charge equilibration time scales smaller than 10 fs and length scales shorter than 10 nm. 14,16,[18][19][20] Sensitivity of electron emission to incident ion charge was shown even for ∼ 100 nm thick carbon foils and attributed to preequilibrium stopping and projectile charge. 21 These experimental observations of pre-equilibrium effects inspired exponential decay models for projectile charge equilibration.…”
Section: Introductionmentioning
confidence: 99%
“…14,18 Since experiments cannot access the projectile's charge state within the material, studies evaluating such models typically compare their predictions to measurements of the projectile's charge after transmission through the sample. 14,20 However, this exit charge state may not be equivalent to the projectile's charge state inside the material. Overall, the transition and equilibration of the ion into the bulk regime is still poorly understood and requires further study.…”
Section: Introductionmentioning
confidence: 99%
“…Focused ion beams are promising in this context, with several empirical demonstrations of their capability to image [22,23], characterize [24], create point defects in [17,18,25], otherwise alter atomic structure of [19,20,[26][27][28][29][30][31], and tune mechanical [25] and electronic [29] properties of 2D materials. However, ion beam parameters must be specially tuned for 2D materials because they exhibit a highly pre-equilibrium response to ion irradiation which differs from bulk and thin films: Highly-charged ions partially neutralize [32,33] and reach an equilibrium charge state only after traversing ∼10 nm of material [34,35], leading to deviations from bulk behavior for atomically thin systems [36]. Even in the case of proton irradiation, surface plasmons are predicted to enhance energy deposition [37], and the radically different plasmonic properties of 2D materials [38,39] should further influence charge and energy transfer processes upon ion impact.…”
mentioning
confidence: 99%